Pembelian Kompulsif Ditinjau dari Kontrol Diri Guru Sekolah Dasar - Siti Maskhuroh; Theda Renanita (Jurnal Ilmu Perilaku, 2018)
The purpose this research to view negative correlation between self-control and compulsive buying of teacher at State Elementary School (SDN) in Kab. Tangerang. This research was conducted at SDN A, B, and C in Kab. Tangerang and use technique total population sampling, mean all of teachers in SDN A, B, and C as population this research is 46 teachers. Method use this research is quantitative with correlation test pearson products moments. Pearson products moments used for view negative correlation between self-control with compulsive buying of teacher at State Elementary School (SDN) A, B, and C in Kab. Tangerang. This research use compulsive buying scale adaptation from Faber & O’Guinn (1992) α = 0.870 and self-control scale adaptation from Tangney, Baumeister, & Boone (2004) α = 0.890. Result correlation test indicated negative correlation between self-control and compulsive buying of teacher at State Elementary School (SDN) in Kab. Tangerang.